STRATEGIES AND VULNERABILITIES IN CROWDFUNDING FOR INNOVATIVE FIRMS - BOZINTAN (COSMA-GULER) IOANA-CARMEN; BADULESCU DANIEL (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2025)
This paper explores the role of crowdfunding in the financing of small and innovative companies, highlighting its importance in filling the gap of traditional financing and in stimulating innovation, challenges particularly visible after the financial crisis of 2008. The main objective is to identify the factors that contribute to the success of crowdfunding campaigns for innovative SMEs. We did this mainly by reviewing the existing literature and then by an assessment of the critical factors for the success of crowdfunding campaigns, such as the quality of the project presentation, the use of social networks, the involvement of qualified investors and the setting of realistic funding goals, but also stressing the importance of a constant communication and post-campaign support. The results show that the success of crowdfunding campaigns depends on a harmonious combination between the attractive presentation of the project, the active involvement of supporters and effective marketing strategies. We have also identified the main vulnerabilities in the financing of innovative companies and projects, such as financial risks or lack of transparency, which can be mitigated through a rigorous planning of the stages or the protection of intellectual property. The usefulness of the research lies in offering practical recommendations for entrepreneurs and investors, highlighting the importance of transparency and trust in financing products through crowdfunding. Undoubtedly, crowdfunding has significant potential to support innovation and economic growth, but its success depends on a number of interrelated factors. As this type of funding continues to develop and mature, further research is needed to fully understand its impact on innovation and entrepreneurship.